Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1962
DOI: 10.1055/s-0038-1655475
|View full text |Cite
|
Sign up to set email alerts
|

Clot Component Reacting with Thrombin

Abstract: SummaryThe fibrin clot induced by a minimum amount of thrombin contains two components: one which forms the fibrin polymer spontaneously and another which does not form the polymer except in the presence of thrombin. The latter component produces non-protein nitrogen like fibrinogen itself, when reacting with thrombin. It is reasonable to conclude that the fissile component of the clot is an intermediate product of the fibrin formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The studies of Laki and Mommaerts 32 33 34 indicated that the conversion of fibrinogen to fibrin occurs in two steps: thrombin first reacts with fibrinogen, and prepares, in some way, for polymerization, which occurs only when the ionic milieu is suitable. Furthermore, the studies of Lorand 35 and Kowarzyk 36 on the release of nonprotein nitrogen during clotting of purified fibrinogen, and the studies on the electrophoretic mobility of fibrinogen and fibrin in urea solutions by Mihalyi 37 also indicated that a change in the fibrinogen molecule had occurred during the transformation.…”
Section: Historical Perspectivementioning
confidence: 99%
“…The studies of Laki and Mommaerts 32 33 34 indicated that the conversion of fibrinogen to fibrin occurs in two steps: thrombin first reacts with fibrinogen, and prepares, in some way, for polymerization, which occurs only when the ionic milieu is suitable. Furthermore, the studies of Lorand 35 and Kowarzyk 36 on the release of nonprotein nitrogen during clotting of purified fibrinogen, and the studies on the electrophoretic mobility of fibrinogen and fibrin in urea solutions by Mihalyi 37 also indicated that a change in the fibrinogen molecule had occurred during the transformation.…”
Section: Historical Perspectivementioning
confidence: 99%